2013
DOI: 10.1007/s00436-013-3301-y
|View full text |Cite
|
Sign up to set email alerts
|

Homogeneity of Trypanosoma cruzi I, II, and III populations and the overlap of wild and domestic transmission cycles by Triatoma brasiliensis in northeastern Brazil

Abstract: The genetic variability of 24 Trypanosoma cruzi isolates from humans (11) and triatomines (13) in northeastern Brazil was analyzed by random amplified polymorphic DNA (RAPD) and compared with taxonomic groups, host, and geographical origin of the parasite. TcI (12.5%), TcII (45.8%), and TcIII (41.6%) showed a similarity coefficient (SC) of 0.74 using the mean of three primers and 0.80, 0.75, and 0.66 for λgt11-F, M13-40F, and L15996 primers, respectively. The samples were clustered according to their phylogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 69 publications
3
12
0
Order By: Relevance
“…More recently, León et al 56 suggested the subdivision of TcI only into two main groups (TcI DOM and sylvatic), proposing a PCR assay for identifying them. In the present study, the sequencing analysis of the TcI isolate (CT-IOC 541) showed that it is genetically closer to Sylvio X10, a stock identified as TcId 60 , a sub-group related to sylvatic cycles, which was also found by Câmara et al 38 in Northeastern Brazil. It is worth mentioning that TcId (or TcI sylvatic) was identified in the heart and brain of patients with severe Chagas disease outside Brazil 46,49 .…”
supporting
confidence: 82%
See 1 more Smart Citation
“…More recently, León et al 56 suggested the subdivision of TcI only into two main groups (TcI DOM and sylvatic), proposing a PCR assay for identifying them. In the present study, the sequencing analysis of the TcI isolate (CT-IOC 541) showed that it is genetically closer to Sylvio X10, a stock identified as TcId 60 , a sub-group related to sylvatic cycles, which was also found by Câmara et al 38 in Northeastern Brazil. It is worth mentioning that TcId (or TcI sylvatic) was identified in the heart and brain of patients with severe Chagas disease outside Brazil 46,49 .…”
supporting
confidence: 82%
“…A sequencing assay followed by BLAST analysis displayed its higher genetic similarity (99%) with several TcI strains, first Sylvio X10, a stock originally of a human case from the Pará State (Northern Brazil), besides a Tcbat stock 16,17 . The genotype TcI had already been found in two patients from the Paraíba State by Barnabé et al 37 , and in three individuals from another close State (Rio Grande do Norte) by Câmara et al 38 . However, these authors did not mention their clinical forms.…”
Section: Discussionmentioning
confidence: 76%
“…It is possible that these changes may be associated with the wide geographical dispersion of homogeneous T. cruzi genotypes from different parasite sources and groups that have been identifi ed throughout the municipalities of RN (60) . As a result, the forms of chronic ChD seem to be directly associated with discrete typing units of T. cruzi, which might explain the observed differences in the expression of anti-infl ammatory and pro-infl ammatory cytokines, and the specifi c immune responses (61) .…”
Section: Discussionmentioning
confidence: 99%
“…Previous fi ndings showed these DTUs circulating in these species in the semiarid zone of RN (15) (17) and highlight the need to understand T. cruzi population distribution in this area. Naturally heterogeneous T. cruzi populations involving TcI, TcII, and TcIII circulate among humans and triatomines in three different municipalities without domicile colonization (17) , and high genetic similarities exist among T. cruzi populations circulating in different hosts, localities, and environments (16) . TcII was detected in the peridomicile in Caicó and in the wild in Serra Negra do Norte, indicating its participation in sylvatic and peridomestic cycles.…”
Section: Discussionmentioning
confidence: 99%
“…Considered the main vector of T. cruzi in the Northeastern semiarid regions, it colonizes both sylvatic and domestic environments but is more frequently captured in peridomestic areas (5) (8) (9) (10) (11) . Triatomine control remains problematic as this region is the center of dispersion and has higher T. brasiliensis concentrations (12) (13) (14) ; it is further aggravated by local vector control activity discontinuation and wild and domestic environmental overlap (15) (16) (17) . Triatoma pseudomaculata also demonstrates high domiciliation capacity,…”
mentioning
confidence: 99%